Path Analysis: Factors Influencing The Students Quality of Life at Pesantren X - Isyrofi, Atik Qurrota A Yunin Al; Afridah, Wiwik; Radhiena Kusuma Wicitra (Universitas Nahdlatul Ulama Surabaya, 2025)
Islamic boarding schools (Pondok Pesantren) play a crucial role in the Islamic education system, particularly in shaping the character and identity of students (santri). Although Pondok Pesantren primarily focuses on educational aspects, other essential factors such as health, environment, and students' behavior also deserve attention to achieve a good quality of life for students. The quality of life significantly determines the success of the educational process. This study aims to analyze the determinants of students' quality of life at Pondok Pesantren X using the PRECEDE-PROCEED framework. Data collection was conducted using the Siskestren (Pondok Pesantren Health Survey Information System) website. The data were analyzed using Smart-PLS version 3.0 for Windows. The results show that several factors significantly influence students' quality of life at Pondok Pesantren X. Genetic factors have a significant impact on behavior (p-value: 0.000) and health (p-value: 0.000). Additionally, a significant influence was found between behavior and health (p-value: 0.000). Furthermore, the study identified a significant influence of environmental factors on health (p-value: 0.010) and a significant impact of health on students' quality of life (p-value: 0.037). Therefore, strategies to improve students' quality of life at Pondok Pesantren X should consider these significant factors, particularly health, behavior, and environment. Keywords: Determinant factors, quality of life, students (santri), pesantren